Hubungan Tingkat Pendidikan dengan Pengetahuan tentang Kontaminasi Arsen (As) pada Kerang Darah (Anadara granosa) di Pasar Tradisional Surabaya Utara - Andini, Niken; Hasanah, Nur; Mahmudiono, Trias (Media Gizi Kesmas, 2024)
Background: Arsenic is one of the dangerous pollutant elements. Arsenic accumulated in clams and consumed by humans with a fairly frequent frequency will result in the accumulation in the body. Objectives: The purpose of this study is to analyze the relationship between education level and knowledge about arsenic contamination in blood clams sold in traditional markets at North Surabaya. Methods: This type of research was a quantitative analytical observational research with a cross sectional approach method that used primary data from direct interviewed and secondary data from previous research literature studies. The sample used was 35 blood clam sellers taken randomly with simple random sampling. The dependent variable in this study is the seller's knowledge and the independent variable is the level of education of blood clam traders. The data obtained were analyzed using the chi-square test. Results: The chi-square analysis revealed that the seller's knowledge is not significant with the seller's education level (p > 0,001). Conclusion: In conclusion, there are no correlation between education level and knowledge about arsenic contamination in blood clams sellers at traditional markets in North Surabaya.